Two sides of the same coin or two different coins? Exploring the duality of corruption in Latin America - Ella Hugo; David Savage; Friedrich Schneider; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
The ambiguous phenomenon of corruption has long been the cause of great theoretical debate in economics. By using Structural Equation Modelling, with the two types of corruption as a latent variable, this paper employs causal and indicative variables specific to the Latin American region to test for rent seeking and systemic corruption in the period between 1980-2018. The findings provide evidence for two types of corruption, one generated by greed, and the other a solution to market failures. Such results support the view that corruption encompasses a complex set of social behaviours.
Keywords: D73; H3; K42; O17; O5; 330; Rent Seeking Corruption; Systemic Corruption; Shadow Economy; Latin America